Analisis Kesulitan Dalam Menyelesaikan Soal Cerita Sistem Persamaan Linear Dua Variabel Siswa Kelas X Akuntansi Di SMK Negeri 1 Tenga - Grachiella Aurelia Baweleng; Anetha L.F. Tilaar; Sylvia Jane Annatje Sumarauw (Departement of Mathematics Education, 2023)
Mathematics is a very important science because human activities generally use mathematics. Mathematics itself is a subject that is taught from elementary school to university. Based on observations made by researchers, most students were unable to understand mathematical concepts, this caused students to experience many difficulties and make mistakes in working on math problems. Besides that, many students experience difficulties when memorizing formulas in learning mathematics. The purpose of this study was to find out and analyze the difficulties and factors that cause students' difficulties in working on word problems on a system of two-variable linear equations. The type of research used is qualitative research. The approach to be used in this research is a descriptive approach. And the results of his research, the average student still has difficulty understanding the basic concepts of mathematics, difficulty understanding concepts, difficulties in solving and calculating steps. Because students still need more guidance and encouragement with students who still encounter many obstacles in solving story problems of a system of two-variable linear equations.